Analisis Yuridis Tentang Status Hukum dan Pengangkatan Anak di Pengadillan Negeri Karawang: Studi Putusan Nomor 175/Pdt.P/2024/PN.Kwg - Mochammad Adi Alamsyach Fadillah; Farhan Asyhadi; Muhamad Abas (Universitas Proklamasi 45, 2025)
Adoption functions as a formal legal process aimed at protecting children’s rights and welfare, especially for those without parental care from their birth parents. It aims to provide legal security, familial stability, and social protection for adopted children within a legitimate family structure. This study presents a normative legal analysis of the procedural aspects of child adoption and critically examines the judicial considerations outlined in the Decision of the Karawang District Court Number 175/Pdt.P/2024/PN.Kwg. Employing a normative juridical approach combined with a case study and conceptual analysis, the research finds that the adoption application submitted by Silwanus Betti and Maria Agustina Kono complies with both formal and material legal requirements. The judge took into account the child’s background, born to a single mother facing economic hardship, and emphasized the best-interests of the child principle. The petition was supported by authentic documents and credible witness testimonies. The court’s ruling not only provides legal legitimacy and protection for the adopted child but also establishes legal certainty for all parties involved in the adoptive family relationship.